2020
DOI: 10.21608/aprh.2020.29194.1106
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaSPM-1 and blaSIM-2 Metallo-β-Lactamases Genes in Imipenem-Resistant Pseudomonas aeruginosa Clinical Isolates Recovered from Two University Hospitals in Egypt

Abstract: Objectives: Unraveling mechanisms whereby Pseudomonas aeruginosa becomes resistant to carbapenems through testing 114 non-duplicate P. aeruginosa clinical isolates for their susceptibility to various classes of antibiotics and scrutinizing the production of metallo-β-lactamases (MBLs) by tested isolates. Methods: Susceptibility testing of P. aeruginosa to different antibiotics was determined by Kirby-Bauer disk diffusion method and MBLs production by tested isolates was studied phenotypically and genotypically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…This low rate is consistent with the research of Elbadawi et al [36] but differs from previous studies that showed a higher prevalence of this gene (82 %) [37]. We reported a low prevalence of blaSPM-1 and blaSIM-1 in this study (3.6 % and 1.8 % respectively) which agreed generally with previous studies but with different percentages (1.75% [38] and 4% [39] respectively. In the current study, the gene blaGIM-1 was not detected among CR GNB isolates, which agrees with the prior Turkish study [40].…”
Section: Discussionsupporting
confidence: 89%
“…This low rate is consistent with the research of Elbadawi et al [36] but differs from previous studies that showed a higher prevalence of this gene (82 %) [37]. We reported a low prevalence of blaSPM-1 and blaSIM-1 in this study (3.6 % and 1.8 % respectively) which agreed generally with previous studies but with different percentages (1.75% [38] and 4% [39] respectively. In the current study, the gene blaGIM-1 was not detected among CR GNB isolates, which agrees with the prior Turkish study [40].…”
Section: Discussionsupporting
confidence: 89%
“…It is of interest that SIM-1 was produced by one strain of MDR K. pneumoniae intermediately susceptible to aztreonam and colistin. Similar results were reported for the SIM-1 gene in A. baumannii 10 in Iraq 22 and in Egypt, 20 in P. aeruginosa and recently in Egypt 23 and K. pneumoniae with ST23 strain carrying SIM-1 in China. 24 The GIM-1 and SIM-1 genes were transferred to Sudan, these can be broadly categorized into issues of emergence, spread, and clonal expansion with diversity, which include natural genetic diversification caused by mutation, horizontal gene transfer among other species, an increase in international travel and patient transfer between countries raising the possibility for further dissemination of strains carrying resistant genes.…”
Section: Discussionsupporting
confidence: 86%
“…Primers that have been used to detect carbapenems-resistant genes in the heteroresistant isolates of interest were designed as previously described by Laurent and coworkers [39]. Primers sequences are listed in Table 1.…”
Section: Qualitative Analysis Of Bio Lm Productionmentioning
confidence: 99%